A three-dimensionally chitin nanofiber/carbon nanotube hydrogel network for foldable conductive paper. (10th December 2015) - Chen, Chuchu; Yang, Chuang; Li, Suiyi; Li, Dagang
Highlights: ChNF/MWCNT nanocomposite was prepared through vacuum filteration. A hybrid hydrogel system was applied to fabricate the ChNF/MWCNT gel-film. Gelation process provided the gel-film twice higher conductivity. The foldable gel-film formed a three-dimensional nano-network structure. Abstract: We reported a highly conductive nanocomposite made with multiwalled carbon nanotubes (MWCNTs) and chitin nanofibers (ChNFs). The MWCNTs were dispersed into ChNFs by the simple process of vacuum-filtration, forming a three-dimensional network structure. In this approach, MWCNT acted as a filler to introduce electron channel paths throughout the ChNF skeleton. And then, a hybrid hydrogel system (20 wt.% NaOH, −18 °C) was applied to prepare the ChNF/MWCNT gel-film followed with drying process. It is found that the resultant ChNF/MWCNT gel-film exposed much more MWCNT areas forming denser structure due to the shrinking of ChNFs after the gelation treatment. Compared with ChNF/MWCNT film, the one treated under hydrogel system (ChNF/MWCNT gel-film) exhibited almost twice higher conductivity (9.3 S/cm for 50 wt.% MWCNTs in gel-film; whereas 4.7 S/cm for 50 wt.% MWCNTs in film). Moreover, the facile and low-cost of this conductive paper may have great potential in development of foldable electronic devices.